Self-concept and intrinsic motivation in foreign language learning: The connection between flow and the L2 self - Marszalek, Jacob M.; Balagna, Diane; Kim, Alissa K.; Patel, Shivani A. (Frontiers in Education, 2022)
An increasingly globalized economy requires a workforce with multilingual capability. However, the United States education system has de-emphasized foreign language learning, such as in the No Child Left Behind Act (NCLB), hurting the recruitment and retention of foreign language learners. To compensate, educators may be able to increase the retention of foreign language learners by fostering intrinsic motivation, but not much currently is known about relevant factors. The present study examined the association of intrinsic motivation and one relevant factor, dispositional flow, in foreign language learners. A sample of 116 foreign language learners was administered the L2 Motivational Self Scale and the Dispositional Flow Scale-2. Good evidence of construct validity was obtained for the scale scores, and a significant positive correlation of .45 was found between the constructs using confirmatory factor analysis. The results suggest dispositional flow is an important factor to consider for increasing intrinsic motivation in foreign language learners.